The effect of high dilutions of Pulsatilla nigricans on the vigour of soybean seeds subjected to accelerated aging - doi: 10.4025/actasciagron.v34i2.13043 - Silva, Hingrid Ariane da; Valderrama, Angela Parizotto; Moreira, Flavia Carolina; Marques, Rosimar Maria; Reis, Bruno; Bonato, Carlos Moacir (Acta Scientiarum. Agronomy, 2011)
The aim of this study was to evaluate the effect of high dilutions of Pulsatilla nigricans in dinamisations 6, 12, 18, 24 and 30 CH on the vigour of soybean seeds subjected to accelerated aging. The experiment was conducted according to a randomised design with 6 treatments and 10 replicates. The treatments consisted of dinamisations 6, 12, 18, 24 and 30 CH and a distilled-water control. After the treatments, the seeds were subjected to accelerated aging (48h at 42ºC) in a growth chamber (25 ± 2ºC). The study evaluated the germination, the length of primary roots and shoots, the fresh weight of roots and shoots and the enzymatic activity of peroxidase (POX-EC1.11.1.7). The variables were analysed by ANOVA, and the means were compared using the Scott-Knott test (p = 0.05). The germination and the fresh weight of roots and shoots of the seedlings treated with Pulsatilla nigricans were higher than the water control, except that CH 30 did not significantly increase the fresh weight of shoots. The dinamisations 6, 24 and 30 CH produced a lower primary root length compared with the control. The dinamisations 12, 18 and 30 CH yielded a greater length of shoots. The total length of seedlings was reduced by the high dilutions 6 and 24 CH.